AUXIN BINDING PROTEIN1 Links Cell Wall Remodeling, Auxin Signaling, and Cell Expansion in Arabidopsis . Issue 1 (14th January 2014) - Paque, Sébastien; Mouille, Grégory; Grandont, Laurie; Alabadí, David; Gaertner, Cyril; Goyallon, Arnaud; Muller, Philippe; Primard-Brisset, Catherine; Sormani, Rodnay; Blázquez, Miguel A.; Perrot-Rechenmann, Catherine
Abstract : This work examines the consequences of inactivation of the auxin receptor AUXIN BINDING PROTEIN1 and identifies alterations in the transcriptome, cell expansion, cell wall remodeling, and xyloglucan structure. It also reveals the importance of modifications of xyloglucan structure in the cell wall for cell expansion. Abstract: Cell expansion is an increase in cell size and thus plays an essential role in plant growth and development. Phytohormones and the primary plant cell wall play major roles in the complex process of cell expansion. In shoot tissues, cell expansion requires the auxin receptor AUXIN BINDING PROTEIN1 (ABP1), but the mechanism by which ABP1 affects expansion remains unknown. We analyzed the effect of functional inactivation of ABP1 on transcriptomic changes in dark-grown hypocotyls and investigated the consequences of gene expression on cell wall composition and cell expansion. Molecular and genetic evidence indicates that ABP1 affects the expression of a broad range of cell wall–related genes, especially cell wall remodeling genes, mainly via an SCF TIR/AFB -dependent pathway. ABP1 also functions in the modulation of hemicellulose xyloglucan structure. Furthermore, fucosidase-mediated defucosylation of xyloglucan, but not biosynthesis of nonfucosylated xyloglucan, rescued dark-grown hypocotyl lengthening of ABP1 knockdown seedlings. In muro remodeling of xyloglucan side chains via an ABP1-dependent pathway appears to be of critical importance for temporal and spatial control of cell expansion.